Presentation of the "PEML Seminars in Ambrosiana" cycle (Prassi Ecdotiche della Modernità Letteraria, 2019)
In the spring of 2019, «Prassi Ecdotiche della Modernità Letteraria», together with the Italian Studies Class of the Ambrosian Academy, organized a series of seminars entitled: Writing, editing, revisions, rewriting: definition problems.The starting point of this proposal comes from a question, which is immediately intertwined with numerous others: is there a difference between «writing» and «redaction», often used as synonyms in philology and in critical pages? If there is a difference, what is the specificity or peculiarity of both of them? What definitions can therefore be given? And, moving in the same direction, until when one can speak of "revision" and when one begins to speak of "rewriting"? And how does a work change by changing its indices? Trying to answer the above questions means either opening a reflection on a possible shared glossary, or dealing with the individual cases that the history of literature or criticism continually presents to scholars.The first two reports of the cycle, which were held in the months of March and April 2019, are therefore proposed in the "Open Conferences" section of this first issue of PEML number 4/1 (2019).